(untitled) (Research, Society and Development, 2022)
The aim of this study was to carry out an integrative literature review on the repercussions of Covid-19 infection in the elderly. To achieve the objective, articles published between 2020 and 2021 were used and were available in the following databases: Sciencedirect, Scielo, Lilacs, Pubmed and Virtual Health Library (VHL). The articles were researched during the months of October and November. Articles published in Portuguese and English were selected. The search resulted in 3,146, but only articles that presented the theme under study were included in the title. Duplicate articles that did not fit the objective of the research were excluded. After the filtration process, 12 articles were chosen to compose the universe of Analysis. The natural aging process includes changes at the cellular level, tissues and organs that contribute to morbidity, frailty and mortality in the elderly population. Elderly patients infected with Sars-Cov-2 have a higher risk of developing more severe symptoms due to reduced telomere size and lymphocyte numbers. Studies have shown that mental disorders correlated with the Covid-19 outbreak include stress, symptoms of depression, anxiety, insomnia, indignation, and fear of the unknown, causing an increased risk of suicide. It was also concluded that the disease caused by Coronavirus is still very recent and some of its repercussions and physiopathology are still unknown. The selected articles did not evaluate the complications after the advancement of vaccine coverage in this population. Thus, we suggest more studies focused on the theme from this year of 2021.